2015
DOI: 10.1007/s10741-015-9517-4
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety as predictors of mortality among heart failure patients: systematic review and meta-analysis

Abstract: Several studies suggest that psychological factors are associated with negative outcomes and in particular higher mortality rates among heart failure (HF) patients. We aimed to evaluate the effect sizes of depression and anxiety on all-cause mortality in HF patients. We conducted a systematic review according to the PRISMA methodology. We searched for studies on depression or anxiety effects on all-cause mortality among HF patients published up to June 2015. A number of 26 and 6 articles met inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
147
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(165 citation statements)
references
References 43 publications
8
147
1
9
Order By: Relevance
“…For patients with HF, depression is associated with an increased rate of adverse outcomes 2,3 , such as hospitalization and death. The aggregated risk-estimate derived from 26 studies was an approximately 1.5-fold risk of death in patients with HF if they had depression (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with HF, depression is associated with an increased rate of adverse outcomes 2,3 , such as hospitalization and death. The aggregated risk-estimate derived from 26 studies was an approximately 1.5-fold risk of death in patients with HF if they had depression (3).…”
Section: Introductionmentioning
confidence: 99%
“…The aggregated risk-estimate derived from 26 studies was an approximately 1.5-fold risk of death in patients with HF if they had depression (3). However, it can be difficult to disentangle whether depression causes a worse outcome, or merely reflects worse HF or more severe co-morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Mental comorbidities such as depressive and anxiety disorders are common in patients with CHF. Depressive comorbidities are present in about 20% of patients, anxiety comorbidities in up to 40% [119].…”
Section: Chronic Heart Failurementioning
confidence: 99%
“…The latest systematic review and meta-analysis reveal prevalence rates of depression and cognitive dysfunction as 29% (10-79%) and 30-80%, respectively, and both are independent predictors of mortality and rehospitalization among HF patients. 3 Recently, it was reported that reduced global CBF predicts depressive symptoms and cognitive dysfunction, and worse outcomes. 4,5 Global CBF is evaluated by transcranial Doppler ultrasonography, radionuclide angiography and magnetic resonance imaging (MRI) (Figure).…”
mentioning
confidence: 99%